Egg quality in different lines of New Hampshire and Giriraja chicken (Bangladesh Journal of Animal Science, 2021)
This study was undertaken to evaluate the egg quality parameters of New Hampshire and Giriraja by maintaining four different flocks (lines) of New Hampshire viz. NH-Khajura, NH-Parwanipur, NH-Khumaltar and NH-Pokhara and three different flocks (lines) of Giriraja viz. GR-Pakhribas, GR-Khumaltar and GR-Tarhara. The 40-60 weeks of hatchability, fertility, external and internal egg quality parameters were studied and recorded. A total of 200 birds (40 weeks of age) of each New Hampshire and Giriraja from each line were maintained on deep litter system. Results from this study indicated the significant effect of genotype and respective lines on fertility and hatchability of eggs. Significant (P